Ecological sustainable physical distribution - Bastian Mrutzek; Herbert Kotzab; André Milosch (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: Increasing online retailing leads to increased transportation processes on individual levels, which is impacting the environment negatively. Consequently, logistics needs ecological sustainable concepts to reduce its anthropogenic emissions, especially in physical distribution. The paper identifies such solutions, which avoid, shift and reduce such emissions and hence improve the environmental impact of logistics. Methodology: For this study, the paper examines 28 relevant papers out of a sample of 219 contributions, with a content-based qualitative literature analysis by applying the methodology suggested by Fink (2010). Findings: Following the fundamental notions of green logistics as proposed by Wittenbrink (2015), the paper identifies various sustainable concepts, which were condensed into a framework of ecological sustainable physical distribution. The overall goals refer to the protection of the atmosphere, decreasing dependence on fossil fuels and conservation of biodiversity. Drivers of such a concept of ecological sustainable physical distribution include horizontal cooperation to avoid, the use of resource-saving transportation means to shift, fleet management and utilisation of alternative fuels to reduce emissions. Originality: This work applies generic strategies for dealing with emissions to the field of physical distribution and presents a first conceptual frame of reference that can be used to implement ecological sustainable notions to the field of physical distribution.
urn:nbn:de:gbv:830-882.0162399; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; Sustainability